PERFORMANCE OF CIVIL SERVANTS IN PUBLIC SERVICE AT THE BIROBULI SELATAN SUB-DISTRICT OFFICE, SOUTH PALU DISTRICT, PALU CITY - Irma, Irma; Chaeriah Ahsan, Sitti; Astrifai, Astrifai (CV. Lafadz Jaya, 2024)
This study aims to explain the performance of civil servants in public services at the Birobuli Selatan Sub-District Office, South Palu District, Palu City. The research adopts a qualitative descriptive method. The study examines how far the performance of civil servants has been implemented in public services at the Birobuli Selatan Sub-District Office, South Palu District, Palu City, using the performance measurement model developed by Agus Dwiyanto (2006:48), which includes the following indicators: work productivity, service quality, responsiveness, responsibility, and accountability. The data used in this study are both primary and secondary. Data collection techniques include observation, interviews, and documentation. The results of this study reveal that the public service performance at the Birobuli Selatan Sub-District Office in administrative services is relatively good in terms of work productivity, responsibility, and accountability. However, the service quality and responsiveness have not fully met the expectations of the public. Citizens have expressed dissatisfaction with the timeliness of services, and the staff's responsiveness in addressing the public's needs is still lacking. Despite these shortcomings, the performance of civil servants is generally deemed acceptable. The findings conclude that, while there are positive indicators in terms of productivity, responsibility, and accountability, improvements are still needed in service quality and responsiveness to ensure better public satisfaction.